The Secretion from Neural Stem Cells Pretreated with Lycopene Protects against tert-Butyl Hydroperoxide-Induced Neuron Oxidative Damage. (22nd July 2018) - Huang, Cuiqin; Gan, Danhui; Fan, Chongzhu; Wen, Caiyan; Li, An; Li, Qin; Zhao, Jiayi; Wang, Zhen; Zhu, Lihong; Lu, Daxiang
Abstract : Neural stem cells (NSCs) hold great potential for the treatment of Alzheimer's disease (AD) through both cellular replacement and their secretion of trophic factors. Lycopene is a potent β -carotenoid antioxidant that has been shown to ameliorate oxidative damage in previous studies. However, it is unclear if lycopene can interact with NSCs to induce the secretion of growth factors, and whether pretreatment with lycopene will allow NSCs to secrete enough trophic factors to reduce oxidative damage to neurons. We pretreated cultured NSCs with lycopene, then applied the lycopene-treated-NSC-conditioned media (Ly-NSC-CM) to primary neuronal cultures exposed to tert -butyl hydroperoxide (t-BHP) to induce oxidative damage. We found that lycopene promoted the secretion of nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), and vascular endothelial growth factor (VEGF) from NSCs. In addition, Ly-NSC-CM attenuated oxidative stress and reduced t-BHP-induced cell apoptosis. We found an antiapoptotic effect related to inhibited expression of Bax/Bcl-2, cytochrome C, and cleaved caspase-3. Moreover, Ly-NSC-CM increased the levels of synaptic proteins, including synaptophysin (SYP) and postsynaptic density 95 (PSD-95), and activated the PI3K/Akt pathway in cultured neurons. Collectively, these data indicate that Ly-NSC-CM could protect neurons from t-BHP-induced oxidative damage.